Agronomic potential of genebank landrace elite accessions for common bean genetic breeding - Bertoldo J.G. (2014)
Plant breeding efficiency relies mainly on genetic diversity and selection to release new cultivars. This study aimed to identify landraces with favorable characteristics that can be used as parents of segregating populations in common bean (Phaseolus vulgaris L.) breeding programs. Firstly, ten bean genotypes were selected because they showed promising agronomic performance, and the following seven adaptive traits of four commercial bean cultivars were evaluated: i) plant height; ii) diameter of the stem; iii) height of the insertion of the first pod; iv) pod number per plant; v) grain number per pod; vi) weight of a thousand grains and vii) grain yield. The accessions BAF 07, BAF 44, and BAF 45 are promising in terms of increasing plant height, and accession BAF 01, in terms of reducing plant height. The accession BAF 07 was also the most promising in terms of a plant ideotype that combines higher plant height, maximum height of the insertion of the first pod, and increment in grain yield. Moreover, the selection can be made between and within accessions, because genetic variability is also present within landraces.